Moya-moya disease in a child with nephropatic cystinosis: a case report and literature review - A. M. Pivovarova; S. V. Papizh; D. O. Kаzakov; K. Z. Gorchkhanovа; I. A. Melnikov (Русский журнал детской неврологии, 2025)
The article presents a case report of a child with a combination of two ultra rare diseases: nephropathic cystinosis and moya-moya disease.Cystinosis is an autosomal recessive lysosomal storage disorder characterized by accumulation of cystine in lysosomes throughout the body. Cystinosis is caused by mutations in the CTNS gene that encodes the lysosomal cystine carrier protein cystinosin. The lack of functional cystinosin causes accumulation and crystallization of cystine within the lysosomes, which leads to apoptosis and tissue damage in all organs. The disease is characterized by renal (Fanconi syndrome with progressive decline in renal function) and extrarenal manifestations in the form of hypothyroidism, hypogonadism, insulin-dependent diabetes mellitus, coronary vascular calcification, metabolic bone disease, damage to the central nervous system with cortical atrophy, cerebral calcification and etc.Moya-moya disease is a progressive condition that can lead to ischemic stroke or intracranial hemorrhage in children and adults. The following types of this condition are distinguished: moya-moya disease primary (idiopathic) refers to patients with angiographic evidence of the disease, who may have a genetic predisposition, but do not have concomitant diseases and moya-moya syndrome – angiographic changes in patients are the same as in patients with moya-moya disease, but there is an underlying disease that is the cause.We analyzed the probable changes in the central nervous system during cystinosis and concluded that the underlying disease cannot be the cause of the identified changes and when observing this patient, we encountered two independent conditions, which required a team approach to determining treatment tactics and further observation.Timely diagnosis made it possible to improve the further prognosis of the disease, but also the patient’s quality of life, stop episodes of cerebral ischemia, and prevent the development of neurological deficits.